Developing a Model for Foot Anthropometric Descriptors for the Design of Prosthesis and Footwear in Nigeria - I.S. Monye; S.A. Omotehinse (Journal of Applied Sciences and Environmental Management)
Foot structure has been known to vary, consequently, there is need for anthropometric data update. The objective of this study is to develop a model of foot anthropometric descriptors for the design of prosthesis and footwear in Nigeria using craft questionnaires structured with Likert’s 5-point attitudinal scale which was administered to 100 respondents and the corresponding data analyzed with Kendall’s Coefficient of Concordance (KCC) and Principal Component Analysis (PCA). Thirteen judges ranked the 36 foot anthropometric descriptors in descending order of importance. The data revealed footwear safety (0.811), technology enhancement (0.811), footwear fitness (0.810), Joint girth (0.794) and change in lifestyle (0.768) as dominant descriptors based on their factor loadings. This study showed that foot anthropometry is an important science for designing prosthetic and foot wears that can achieve the desired fit and comfort.